Differential Sexual Behavior Experiences of LGBQ and Transgender/Nonbinary Young People in Colorado. Issue 3 (April 2021) - Kattari, Shanna K.; Atteberry-Ash, Brittanie; Eugene Walls, N.; Rusow, Joshua; Klemmer, Cary; Kattari, Leonardo
Lesbian, gay, bisexual, transgender, queer and questioning (LGBTQ) youth experience numerous disparities, including but not limited to access to health care, HIV risk, safety in school, educational opportunities, and family support. Historically, research on this community lumped together LGBQ experiences with experiences of transgender and nonbinary (trans/NB) individuals, despite sexual orientation and gender identity being unique identities. Using representative statewide data from the 2015 Healthy Kids Colorado Survey (HKCS) ( N = 15, 970), this study examines sexual behaviors through a more nuanced and intersectional lens. We find that young LGBQ and trans/NB people in Colorado have differential experiences of sexual behavior compared with their heterosexual and cisgender counterparts. Being LGBQ and especially being trans/NB, having current depression, suicidal ideation, and experiencing electronic bullying are all associated with an increase in the likelihood of ever having sex and total number of partners, and lower age of sexual debut. These findings and their implications highlight the importance of inclusive sexuality education and culturally responsive services for all young people.